1999
DOI: 10.1021/ja9901011
|View full text |Cite
|
Sign up to set email alerts
|

Control of Monolayer Assembly Structure by Hydrogen Bonding Rather Than by Adsorbate−Substrate Templating

Abstract: Stratified amide-containing self-assembled monolayers (SAMs) provide opportunities for investigating the fundamental dependence of supramolecular structure upon molecular constitution. We report a series of amide-containing alkanethiol SAMs (C n -1AT/Au, n = 9, 11−16, 18) in which the hydrophobic overlayer thickness is systematically varied and the thickness of the polar region is held constant. The results from X-ray photoelectron spectroscopy, contact angle goniometry, reflective IR spectroscopy, and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
163
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(178 citation statements)
references
References 80 publications
(166 reference statements)
15
163
0
Order By: Relevance
“…22 In the TegA/MHA system intermolecular H-bonds between amide groups of neighboring TegA ligands ( Figure 5) 23,45 must drive phase separation in the ligand shell, as expected from simulations (Figure 3a).…”
Section: Since Our Partially (Figures 3a-d) and Fully (Figures 3e-h) mentioning
confidence: 62%
“…22 In the TegA/MHA system intermolecular H-bonds between amide groups of neighboring TegA ligands ( Figure 5) 23,45 must drive phase separation in the ligand shell, as expected from simulations (Figure 3a).…”
Section: Since Our Partially (Figures 3a-d) and Fully (Figures 3e-h) mentioning
confidence: 62%
“…We are thus constrained to use relatively small R groups, where the molecular order of these groups in the SAM is not established, but is almost certainly less than in n-alkanethiolates. [51][52][53][54]77 Whatever the reason, the data in Figures 1 and 2 rates of tunneling. 56 The theory of tunneling through junctions containing SAMs is not sufficiently developed at present to give any guidance to these studies, and it is not clear whether this low sensitivity is expected or not.…”
Section: Figmentioning
confidence: 99%
“…The amide group (-CONH-) is one of the best understood in organic chemistry, 49,50 and while not isostructural with -CH 2 CH 2 -is similar in size, and is known, from prior work, to be compatible with the formation of SAMs. [51][52][53][54][55] ii) Perhaps more importantly, we wished to develop a system of SAMs to use in studies of charge transport that was more easily modified structurally than are derivatives of n-alkanethiolates. Preparing compounds of the structure HS(CH 2 ) n R, where n is 10 -20, and R is a group that we might wish to select, with as few restrictions as possible, from the full range of organic and organometallic groups, can be synthetically arduous.…”
Section: Introductionmentioning
confidence: 99%
“…Clegg and coworkers prepared a series of SAMs of amide-containing alkanethiols on a Au substrate 5 [39,40]. Using the results of IR reflection-absorption spectral measurements, they revealed that the amide-containing alkanethiol molecules form extended hydrogen bonding networks and that the existence of amide group disrupts the ordering of the alkyl chains due to the steric effect.…”
Section: Methodsmentioning
confidence: 99%